BREAST MILK AS A GOLD STANDARD FOR DEVELOPMENT OF ARTIFICIAL MILK FORMULAS - O. L. Lukoyanova (Вопросы современной педиатрии)
The current data of the scientific research of breast milk composition are represented in this article. The author produces proofs of the necessity of inclusion into artificial formulas different functional components found in breast milk. There are also shown the main principles of artificial milk formulas adaptation.